49 - (x 2 - 3) = x 4 - 6x 2 + 9

Which of the following equations is equivalent to the equation above, if z = x 2 - 3?

Thank you for the opportunity to help you with your question! I'll show you step by stp.

40 - (x^2 - 3) = x^4 - 6x^2 + 9

z = x^2 - 3, then equation becomes

49 - z = x^4 - 6x^2 + 9

49 - z = (x^2 - 3)^2 (factored)

49 - z = z^2

z^2+ z - 49 = 0

This is the final equation when z=x^2 - 3

Secure Information

Content will be erased after question is completed.

Enter the email address associated with your account, and we will email you a link to reset your password.

Forgot your password?

Sign Up